KONTRIBUSI PEMAHAMAN KOSAKATA BIDANG JURNALISTIK TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 25 PADANG - Salsa Bila; Mohd. Hafrison (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research has the following objectives. First, to describe the level of vocabulary mastery in journalism for eighth grade students of SMP Negeri 25 Padang. Second, to describe the skill level of writing news texts for eighth grade students of SMP Negeri 25 Padang. Third, to describe the contribution of vocabulary mastery in the field of journalism to the writing skills of the eighth grade students of SMP Negeri 25 Padang. This research is a quantitative research with descriptive methods and uses a correlational research design. The population in this study were students of class VIII SMP Negeri 25 Padang who were registered in the 2020/2021 academic year, totaling 252 students from 8 classes and 63 samples. The sampling technique used was proportional random sampling, namely sampling based on the number of student proportions per class. In this study, the independent variable (X) is the vocabulary mastery of journalism for the eighth grade students of SMP Negeri 25 Padang and the dependent variable (Y) is the writing skills for the eighth grade students of SMP Negeri 25 Padang. Based on the results of the analysis and explanation of the data, three conclusions were drawn. First, the vocabulary mastery of journalistic vocabulary for the eighth grade students of SMP Negeri 25 Padang in good qualifications (84.37). Second, the skills in writing news texts of the eighth grade students of SMP Negeri 25 Padang are in good qualifications (82.14). Third, mastery of environmental vocabulary contributes to the skills of writing news texts in class VIII students of SMP Negeri 25 Padang. However, skills in writing news texts require mastery of journalistic vocabulary. Kata Kunci : kontribusi, pemahaman kosakata bidang jurnalistik, keterampilan menulis teks berita.